THE IMPACT OF COGNITIVE BIASES ON RETAIL INVESTOR DECISION-MAKING IN VOLATILE MARKETS - Norqulova Sevinch Asliddin qizi (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract: This study investigates the role of cognitive biases in shaping retail investor decision-making under conditions of market volatility. While traditional financial theories emphasize rationality and efficiency, increasing empirical evidence from Behavioral Finance suggests that investors are systematically influenced by psychological biases. This research focuses on three major cognitive biases— overconfidence, loss aversion, and herd behavior—and examines their impact on investment decisions and portfolio outcomes. Using a quantitative research design, data collected from retail investors is analyzed through regression and correlation techniques. The results reveal that cognitive biases significantly affect decision quality, often leading to excessive trading, poor risk management, and suboptimal returns. The study contributes to both theory and practice by highlighting the need for behavioral awareness and structured investment strategies in volatile market environments.